An Analysis of Slang Word Formation in Ice Cracker Ii (The Emperor’s Edge 1.5) Short Story by Lindsay Buroker - Hardianti Hardianti; Fina Amalia Masri (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
This research used Short Story by Lindsay Buroker as the object material and Slang Word Formation by George Yule’s as a theory. This research aimed to analyze what is the slang word formation in Ice Cracker II (The Emperor’s Edge 1.5) Short Story. This research used a qualitative research method. The result of the research shows that there are 11 data found, they are Coinage consists of 2 data, Compounding consists of 2 data, Blending consists of 3 data, Clipping consist of 1 data, Derivation consists of 2 data, and Multiple Process consist of 1 data. The most dominant of slang word formation is Blending. Blending is a combination of two separate word forms to make a single new word term.